AN ANALYSIS OF LEXICAL AND SYNTACTIC FEATURES IN ENGLISH AND INDONESIAN RADIO FOOTBALL COMMENTARY - Fadilah, Isa Rian (perpustakaan.edu, 2015)
This study entitled 'An Analysis of Lexical and Syntactic Features in English and Indonesian Radio Football Commentary' aims to unearth the types of lexical and syntactic features of Sport Announcer Talk (SAT) in English and Indonesian live football commentary broadcast on radio. It applies a qualitative approach with descriptive method in analysing the data. The data are analysed using Kuiper's (2000) formulaic language, Lakoff and Johnsen's (2003) metaphor, Kovecses' (2010) metonymy and Ferguson's (1983) framework of syntactic aspects in Sport Announcer Talk. The findings show that lexical features; formulae, metaphor, and metonymy and syntactic features; simplification, inversion, result expressions, heavy modifiers, routines, and tenses are pervasive in English and Indonesian commentary. These features can be considered as the characteristics of SAT. In addition, this study reveals some differences between English and Indonesian commentary. First, Indonesian sportscasters use formulae to express event and non-event commentary, whereas English sportscasters use formulae to report events only. Second, English sportscasters employ metonymy as the means of avoiding redundancy and saving time, whereas Indonesian sportscasters utilise metonymy as the way of overcoming the inability to recognise a player at the moment of speaking. Third, English sportscasters apply normal simplification, whereas Indonesian sportscasters happen to use unusual simplification; a very minimum word to express a certain event. There exists an issue of high context communication in simplification of Indonesian commentary. This leads to a conclusion that the use of such lexical and syntactic features accommodates the sportscasters to be able to maintain fluency in performing commentary.